Stop, look, listen (to the drivers) an analysis of bus and utility vehicle (UV) express drivers' language preference for traffic signs - Cabaluna, Cedrick C.; Saqueton, Grace M. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2018)
The study determined the attitudes and language preference of Filipino bus and utility (UV) drivers concerning traffic signs found in Manila and Quezon City. Attitudes were determined using the notion of non-market values: direct use values, indirect use values, bequest values, and existence value, which in turn determined the driers' language preference among Filipino, English, and bilingual traffic signs. The study utilized the Contingent Valuation Method (CVM) with the Likert scale in making survey questionnaires which served as the main instrument in gathering data. For the descriptive presentation of the data, frequency and percentage were used to exhibit the features of the traffic signs. Mean and standard deviation were used to show the value attribution of the drivers. T-test was used to determine the difference between drivers who answered Filipino survey questionnaires and drivers who answered English survey questionnaires. Pearson Moment Correlation was used to determine the relationship between the drivers and their preferred language in traffic signs. The following findings were obtained: the traffic signs were mostly top-down, warning notices and prohibitions, and are written in English. Drivers valued Filipino more than English in most of the value categories, and the drivers generally preferred traffic signs in Filipino only over traffic signs in English only, but preferred bilingual traffic signs over Filipino only signs.
Thesis (B.A. in English Studies : Language)--University of the Philippines Diliman
Includes bibliographical references and appendices.